Strategies for Civil Servants to Navigate Local Political Dynamics: A Case Study of X Regency - Mario Roberto; Astika Ummy Athahirah (Green Publisher Indonesia, 2026)
The phenomenon of the vulnerability of the career of State Civil Apparatus (ASN) due to regional political dynamics often creates great pressure that tests their integrity and impartiality, especially because of their position that is vulnerable to informal political practices. This research explored the coping mechanism developed by bureaucrats in Regency X, Papua Province, in dealing with the dynamics of political leadership. Using a qualitative approach with an exploratory case study design, data was collected through in-depth interviews with informants from various levels of position. The results of the study show that civil servants in Regency X develop a hybrid survival strategy by combining administrative adaptation and local socio-cultural forces to ensure their career stability. Bureaucrats control political pressure through a combination of proving loyalty, strengthening professionalism, and withdrawing to avoid the risk of mutation. A significant finding in this study is the emergence of another form of moving against strategy that functions as a